Nursing Students' Perceptions, Knowledge, and Preventive Behaviors Toward COVID-19: A Multi-University Study - Hamdan Mohammad Albaqawi; Nahed Alquwez; Ejercito Balay-odao; Junel Bryan Bajet; Hawa Alabdulaziz; Fatmah Alsolami; Regie B. Tumala; Abdalkarem F. Alsharari; Hanan M. M. Tork; Ebaa Marwan Felemban; Jonas Preposi Cruz (Frontiers Media S.A., 2020)
Background: Knowledge, perception, and preventive behavior should be considered in the planning of effective educational interventions for the coronavirus disease of 2019 (COVID-19) pandemic and in increasing awareness about the health risks brought about by this disease. This research aimed to assess knowledge, perceptions, and preventive behavior toward the COVID-19 infection among student nurses.Methods: The study has quantitative, descriptive, and cross-sectional design. A convenience sample of 1,226 student nurses from seven universities in Saudi Arabia was surveyed from March 22 to April 4, 2020. A four-part online survey on demographic characteristics, perceptions, knowledge, and preventive behavior of Saudi student nurses was carried out.Results: Nearly all students were aware of the outbreak (99.2%), and most of them received information on COVID-19 primarily from social media (71.0%). Over three-fourths of the students were confident that the government (89.1%) and Ministry of Health (MOH) (86.5%) were doing a good job responding to the COVID-19 outbreak in the country. The overall average score in the knowledge questionnaire was 9.85 (SD = 1.62, range = 0-12), which is equivalent to 82.1%. The majority of the students always performed most of the preventive behavior identified in the survey, except "washing hands with soap and water for at least 20 s after blowing my nose, coughing, or sneezing" (39.2%) and "daily cleaning and disinfecting frequently touched surfaces" (41.6%). Being female, being in the fourth year, and gaining good perceived knowledge were associated with high actual COVID-19 knowledge. University, gender, age, academic level, and perceived COVID-19 knowledge were the associated factors.Conclusions: The findings of this study have provided baseline information on the current state of Saudi nursing students' perceptions, knowledge, and preventive behavior toward COVID-19 as the crisis is happening. The findings revealed some areas that should be focused on by nursing education, as well as health agencies, to ensure that the students have adequate knowledge and correct preventive behavior.